FACTORS INFLUENCING THE COMMUNITY-BASED ECOTOURISM DEVELOPMENT IN CAMBODIA: STRUCTURAL EQUATION MODEL ANALYSIS - Phon, Dr. Samphors; Phon, Sophat; Touch, Visalsok (jfpublisher, 2024)
Community-based ecotourism (CBET) aims to empower local communities through engagement and participation in Cambodia. This study investigates the relationship among tourism destination love, community engagement, socio-cultural attributes, support for CBET, perceived impact likelihood, community economic benefits, and CBET development in ecotourism sites and biodiversity conservation by drawing on a case study of the main eight ecotourism areas in Cambodia. The study used a quantitative research approach to investigate and parameterize the dynamic ecotourism components, and to explore key factors influencing the CBET using a self-administered survey by intercepted 406 visitors and structured questionnaire items were asked local communities who provide tourism services to visitors in eco-tourism destination sites in November 2022 and March 2023. The results of SEM indicated that all relationships among research variables (as proposed in the conceptual model) were significantly impacted and confirmed by this study. This means that CBET requires additional essential support from the resources listed above in order to grow in local communities in Cambodia.